Mode-locked pulse generation from an all-fiberized, Tm-Ho-codoped fiber laser incorporating a graphene oxide-deposited side-polished fiber - Jung, Minwan; Koo, Joonhoi; Park, Jaehyun; Song, Yong-Won; Jhon, Young Min; Lee, Kwanil; Lee, Sangbae; Lee, Ju Han (OPTICAL SOC AMER, 2013)
An in-depth experimental investigation was conducted into the use of a graphene oxide-based saturable absorber implemented on a side-polished fiber platform for femtosecond pulse generation in the 2 mu m region. First, it was experimentally shown that an all-fiberized thulium-holmium (Tm-Ho)-codoped fiber ring laser with reduced cavity length can produce stable femtosecond pulses by incorporating a graphene oxide-deposited side-polished fiber. Second, the measurement accuracy issue in obtaining a precise pulse-width value by use of an autocorrelator together with a silica fiber-based 2 mu m-band amplifier was investigated. It showed that the higher-order soliton compression effect caused by the combination of anomalous dispersion and Kerr nonlinearity can provide incorrect pulse-width information. Third, an experimental investigation into the precise role of the graphene oxide-deposited side-polished fiber was carried out to determine whether its polarization-dependent loss (PDL) can be a substantial contributor to mode-locking through nonlinear polarization rotation. By comparing its performance with that of a gold-deposited side-polished fiber, the PDL contribution to mode-locking was found to be insignificant, and the dominant mode-locking mechanism was shown to be saturable absorption due to mutual interaction between the evanescent field of the oscillated beam and the deposited graphene oxide particles. (C) 2013 Optical Society of America
Keywords: EVANESCENT FIELD INTERACTION; NANOTUBE SATURABLE ABSORBER; CARBON NANOTUBE; AVERAGE SOLITON; WAVE-GUIDE; ULTRAFAST; OPTOELECTRONICS; WAVELENGTH; PHOTONICS; POLARIZER